ANALISIS WORK-LIFE BALANCE DAN KEPUASAN KERJA GURU ANAK USIA DINI DI ERA DIGITAL: STUDI KASUS DI TPA HARAPAN BUNDA KEC. BAWANG - Feny Novia Hariyanti; Barokah Isdaryanti; Joko Sutarto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The digital transformation in early childhood education not only enhances administrative efficiency but also introduces new challenges to the psychological well-being of educators. This study aims to analyze in depth the dynamics of work-life balance (WLB) and job satisfaction among early childhood teachers in the digital era. Employing a qualitative approach with a case study design, this research was conducted at TPA Harapan Bunda, Bawang District. Data were gathered through in-depth interviews with teacher informants (both single and married groups) and key informants, descriptive observations, and documentation studies. Data analysis followed the interactive model of Miles and Huberman, while data validity was ensured through source triangulation, technique triangulation, and member checks. The findings reveal that educational digitalization, such as app-based developmental reporting and intensive online communication via WhatsApp with parents, triggers the phenomenon of blurring boundaries and work-family conflict, particularly among married teachers. Nevertheless, the teachers' job satisfaction level remained fairly good. This satisfaction is strongly sustained by intrinsic factors, namely emotional bonds and a sense of happiness (professional altruism) in nurturing children, as well as extrinsic factors, including a collaborative non-physical work environment and organizational support from the principal. This study confirms a close positive relationship between work-life balance and teacher job satisfaction, where institutional support plays a crucial role as a buffer variable in reducing the pressure of digital workloads. Keywords: Job Satisfaction, Early Childhood Teachers, Digital Era, TPA Harapan Bunda, Work-Life Balance.